TREATMENT OF POSTRAVMATIC REFLEX SYMPATHETIC DYSTROPHY SYNDROME WITH CALCITONIN - D. Ofluoğlu,; G. Akyüz,; Ö. Kayhan,; F. Dede,; H. T. Turoğlu,; TY Erdinc,; S. İnanır, (Archives of Rheumatology, 2003)
Reflex sympathetic dystrophy syndrome (RSDS) is a common but often unrecognized entity. It usually affects extremities after a certain trauma. The purpose of this study was to investigate the effects of calcitonin on pain and symptoms in upper limb RSDS which was seen after a certain trauma. The study included 15 patients with stage I RSDS. Three of 15 were men and 12 were women. Their mean age was 55±15 (25-72). All patients were treated with 200 IU/day intranasal salmon calcitonin for 3 months, and with whirlpool, TENS (Trancutaneous Electrical Nerve Stimulation), 1.5 watt/cm2 ultrasound therapy for 15 days following diagnosis. Range of motion (ROM) exercies were prescribed in warm water and continued for 3 months. Before and after treatment, we measured joint ROM and grasp strength with a goniometer and dinamometer respectively. Patients' pain level was evaluated by using 10 cm visual analogue scale (VAS). Finally, physicians' global assessment was utilized at the end of the study. At the end of the study, ROM, pain scores and grasp strength improved (p<0.05). As a result, we suggested that intranasal salmon calcitonin decreased pain scores and increased functional activity in traumatic reflex sympathetic dystrophy syndrome.